An Investigation of level Applying Environmental sensing strategies in the National Security Advisory : An Empirical Research - Hamed Taheer*, Hussam; Mahdi Saleh, Khalid (Journal of Economics and Administrative Sciences, 2024)
This research aims to diagnose the level of embodiment of environmental sensing strategies in the National Security Advisory in Iraq. The importance of the research is evident from the importance of the topic it deals with. Environmental sensing in its three dimensions (Prediction strategy, scaling strategy, and Lockdown strategy) is one of the crucial issues in the success of organizations of all kinds. In addition to the importance of the researched organization (NSA), which is one of the most important components of ministries and security institutions and its active role in ensuring the security and stability of the country at the national and global levels. The problem of the research is how to read environmental variables by the (NSA) in a proactive manner through which it can make decisions that help it in preparing and drawing operational and strategic plans, as the research question expresses (what is the nature and level of interest in environmental sensing strategies at the NSA). The research included a sample of (90) respondents who hold positions in the NSA, and the questionnaire was used as a main tool for data collection. A group of statistical methods were used supported by the statistical program (SPSS) in order to obtain the results. The most important results were the variation in the embodiment of environmental sensing strategies in the research sample within the (NSA), where the prediction strategy came in order, then the scaling strategy, and finally the Lockdown strategy, respectively. Paper type Research paper